2013
DOI: 10.1186/1471-2334-13-129
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of symptoms and laboratory data for pertussis in adolescent and adult patients

Abstract: BackgroundSeveral symptoms are classically thought to be suggestive of pertussis in children, but the diagnostic value of these symptoms in adolescent and adult patients is unclear. We evaluated the accuracy of the clinical findings for the early presumptive diagnosis of pertussis in adolescent and adult patients. Furthermore, we measured fractional exhaled nitric oxide (FeNO) with regard to whether we could distinguish eosinophilic inflammation of the airway and pertussis. FeNO is not expected to be associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 32 publications
2
27
1
2
Order By: Relevance
“…Wood et al have reported that young infants may initially present with apnea alone (8). A previous study reported the following frequency of symptoms, which is similar to the results of our study: paroxysmal cough, 100z; prolonged cough over 14 days, 43z; inspiratory whoop, 39z; posttussive vomiting, 25z; and apnea, 7z (9). Clinical features, excluding apnea, were observed in unvaccinated and previously vaccinated patients.…”
Section: Discussionsupporting
confidence: 80%
“…Wood et al have reported that young infants may initially present with apnea alone (8). A previous study reported the following frequency of symptoms, which is similar to the results of our study: paroxysmal cough, 100z; prolonged cough over 14 days, 43z; inspiratory whoop, 39z; posttussive vomiting, 25z; and apnea, 7z (9). Clinical features, excluding apnea, were observed in unvaccinated and previously vaccinated patients.…”
Section: Discussionsupporting
confidence: 80%
“…Clinical case definitions vary by country and/or institution (28,29). The specificity of case definitions is negatively influenced by the time between infection and diagnosis, by previous vaccination or infection, and by increasing age of patients (30). Furthermore, the sensitivity of clinical diagnosis is low for adolescents and adults, due to the mitigated presentation of the disease.…”
Section: Diagnosis Case Definitionmentioning
confidence: 99%
“…18,19 O IPPMG não dispõe de material para identificação da B. pertussis. Quando há suspeita e notificação do agravo, procede-se a coleta de material e envio para o laboratório-referência de saúde pú-blica do Rio de Janeiro (Lacen-RJ), o qual disponibiliza o swab e o meio de cultura para coleta.…”
Section: Discussionunclassified
“…Estudos em São Paulo têm mostrado a baixa positividade do exame realizado pela técnica de cultura em relação à técnica de RT-PCR, 22,23 e em outros países a sorologia é apontada como método de maior positividade e pode ser de única amostra de soro no período de duas a oito semanas após o início da tosse, quando o nível de anticorpos atinge seu máximo. 6,24,25 Apesar do não isola mento da B. pertussis, na amostra estudada, sintomas descritos em outros estudos como fortemente associados ao diagnóstico de coqueluche 18,19,26 estavam presentes em nossos pacientes, como tosse persistente, paroxística, cianose, temperatura abaixo de 38 °C e achados laboratoriais inespecíficos, como contagem de linfócitos maior ou igual a 10.000/mm 3 e de leucóci-tos de 20.000/mm 3 ou mais, também descritos na literatura como associados ao diagnóstico de coqueluche confirmada por testes específicos. 27 Neste estudo sete pacientes (11%) evoluíram para óbito.…”
Section: Discussionunclassified